Breeding common bean for resistance to common blight: A review - Singh, Shree P.; Miklas, Phillip N. (Wiley, 2015)
Common blight [caused by Xanthomonas campestris pv. phaseoli Smith (Dye)] is a major bacterial disease causing >40% seed yield and quality losses in common bean (Phaseolus vulgaris L.) worldwide. Use of resistant cultivars is crucial for its effective, economical, and environment friendly integrated management and control. Common blight resistant germplasm are found in the primary, secondary, and tertiary gene pools of the common bean. Substantial progress has been made in understanding the pathogenic variation, germplasm screening methods, identification of resistant germplasm, genetics of resistance, identifying and mapping molecular markers linked with resistance quantitative trait loci (QTL), introgressing resistance from the secondary and tertiary gene pools, transferring resistance from the Middle American common bean landraces to Andean cultivars and germplasm lines, and pyramiding or combining resistance from diverse germplasm sources into common bean. Backcross, pedigree, gamete, and recurrent selection methods or their modifications singularly or in combination have been used to introgress and pyramid resistance. Also, molecular markers with or without direct disease screening have been used for breeding for resistance. However, Andean and Middle American common bean cultivars with high levels of combined resistance to less-aggressive and aggressive bacterial strains in all aerial plant parts are not available. We will review progress achieved in breeding for resistance, briefly describe problems faced, and discuss strategies for integrated genetic improvement for common blight resistance for cultivar development.